Subcommittee on the Accounting Treatment of Changing Prices of the Committee on Financial Accounting Standards. (The Accounting Review, 1977)
Abstract This article presents the text of a report by a subcommittee of the Committee on Financial Accounting Standards of the American Accounting Association which commented on a proposed accounting standard from the International Accounting Standards Committee in the U.S. as of October 2, 1977. The American Accounting Association is composed primarily of accounting educators and researchers in the United States and Canada. This objective of working towards an increasing degree of uniformity and, presumably, comparability among founder and associate member countries is difficult to associate with ED6 in any but a very long run context, if at all. While experimentation with the three alternatives mentioned in ED6 might eventually lead to the presentation of more uniform financial statements, a diversity of approaches are encouraged in the short run. Moreover, it is not clear that the IASC sees ED6 as an interim step on the road to a uniform current value and/or general price-level restated system. The IASC has set out, more clearly than many accountancy bodies, the dual problems that can arise under conditions of changing prices, the problem of taking into account the changing value of the monetary unit during inflation or deflation and the separate problem of allowing for changes in the prices of particular assets and liabilities! while they are held.